Pengaruh Guided Discovery Learning Terhadap Kemampuan Pemecahan Masalah Turunan Dan Integral Mahasiswa Pendidikan Teknik Bangunan Universitas Palangka Raya Tahun 2020/2021 - Revianti Coendraad (Jurnal Ilmiah Kanderang Tingang, 2021)
This research is motivated by the low ability of solving mathematical derivatives and integral problems of building engineering education students. The problem that is often found in teachers is that they still use conventional methods so that students feel bored and are not passionate about learning. The use of models that can make students more interested in paying attention to learning and improving problem solving skills. one of them is Guided Discovery Learning which aims to improve students' problem solving skills. This study aims to determine the application of the Guided Discovery Learning model to building engineering education students, to describe the mathematical problem solving ability of derivatives and integrals, and to determine the effect of the application of the Guided Discovery Learning model to the mathematical problem solving abilities of students of building engineering education. The approach used in this study is a quantitative approach with a Quasi Experimental Design type of research. The independent variable in this study is Guided Discovery Learning, while the dependent variable is problem solving ability. The total population is 20 students of building engineering education in 2020/2021. Data collection techniques used in this study were observation, tests, and documentation. Data were collected by giving pretest, treatment, and posttest. The data analysis technique used the analysis prerequisite test, including the normality test, homogeneity test, and hypothesis testing with the final analysis using the independent sample t test with the SPSS system. The results of this study indicate that Guided Discovery Learning can improve the ability to solve derivative and integral mathematics problems in building engineering education students.